Behaviour in a standardized assay, but not metabolic or growth rate, predicts behavioural variation in an adult aquatic top predator Esox lucius in the wild. Issue 4 (6th March 2016) - Laskowski, K. L.; Monk, C. T.; Polverino, G.; Alós, J.; Nakayama, S.; Staaks, G.; Mehner, T.; Arlinghaus, R.
Abstract : This study tested for links among behaviour, state and life‐history variables as predicted by the pace‐of‐life hypothesis in adult pike Esox lucius. First, a standardized open‐field behavioural assay was developed to assess individual behaviour of wild‐captured adult E. lucius . Behaviour within the standardized assay predicted swimming behaviour in the lake, providing an ecological validation of the assay. There was no relationship between standardized behaviour and any of the life‐history and state variables, including metabolism, body condition, juvenile growth rate and adult growth rate in contrast to predictions from the pace‐of‐life hypothesis. This study demonstrates that it is possible to assess ecologically relevant behavioural variation in a large‐bodied top predator using a standard open‐field assay, but it is noteworthy that this standardized behaviour is not systematically related to standard metabolism or growth.